2010
DOI: 10.1007/s11738-010-0521-y
|View full text |Cite
|
Sign up to set email alerts
|

Responses of growth and antioxidant systems in Carthamus tinctorius L. under water deficit stress

Abstract: An investigation was carried out to find out the extent of changes occurred in two safflower (Carthamus tinctorius L.) cultivars in response to water deficit stress. Two safflower cultivars namely IL.111 and Isfahan were used for the study. Thirty days after sowing, plants were grown under soil moisture corresponding to 100, 85, 70 and 55% field capacity for next 30 days. Water deficit treatments significantly decreased the shoot length, shoot dry matter, root dry matter, relative growth rate, leaf relative wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
43
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 57 publications
8
43
0
1
Order By: Relevance
“…In drought-tolerant plant species, POD activity was found to be sufficiently high to enable the plants to protect themselves against oxidative stress (Fazeli et al 2007, Vaseva et al 2012). Activity of one or more antioxidant enzymes generally increases in plants exposed to drought conditions, and this elevated activity correlates with increased drought tolerance (Srivalli et al 2003, Hojati et al 2011, Hassanpour et al 2012. Findings from the present study showed that POD activity in the tolerant cultivar HST was higher than those in the sensitive one LC15 (Figure 2c).…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…In drought-tolerant plant species, POD activity was found to be sufficiently high to enable the plants to protect themselves against oxidative stress (Fazeli et al 2007, Vaseva et al 2012). Activity of one or more antioxidant enzymes generally increases in plants exposed to drought conditions, and this elevated activity correlates with increased drought tolerance (Srivalli et al 2003, Hojati et al 2011, Hassanpour et al 2012. Findings from the present study showed that POD activity in the tolerant cultivar HST was higher than those in the sensitive one LC15 (Figure 2c).…”
Section: Resultssupporting
confidence: 50%
“…Findings from the present study showed that POD activity in the tolerant cultivar HST was higher than those in the sensitive one LC15 (Figure 2c). A number of studies indicated that POD activity response to osmotic stress vary among plant species and among different cultivars (Hojati et al 2011). It is concluded that the higher activity of POD in the tolerant cultivar HST might be better to protect proteins, chlorophyll and lipids of some parts of plants against ROS attack compared to that in the sensitive LC15.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increase in CAT activity has also been reported in other plants (Anjum et al, 2011;Huseynova, 2012). Hojati et al, 2011). During water stress, especially in 25% FC, both pomegranate cultivars ('Rabbab' and 'Shishehgap') showed high activity of SOD, APX and CAT enzymes.…”
Section: Discussionsupporting
confidence: 54%
“…The current results also showed perchlorate addition significantly increased POD activity at tillering stage, but there was no significant difference at heading stage. A number of studies indicated that POD activity response to environmental stress vary among plant species and among different cultivars [36,37].…”
Section: Differential Responses Of Twomentioning
confidence: 99%